2013
DOI: 10.1007/s12687-013-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered incidence of meiotic errors and Down syndrome birth under extreme low socioeconomic exposure in the Sundarban area of India

Abstract: We conducted a survey to analyze the genetic epidemiology of trisomy 21 Down syndrome births in the Sundarban delta region of India. In this region, inhabitants are chiefly from marginalized poor tribal communities and have lived in extremely low socioeconomic condition for several generations. Microsatellite genotyping revealed an meiosis I/meiosis II ratio that is different from the previous reports on the Down syndrome populations from other parts of the world. Analyses of distribution of achiasmate nondisj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In Egypt, like other Middle Eastern countries, consanguinity rates fluctuate depending mainly on religious as well as cultural morals, especially in rural areas [22,24]. In the current study, by comparison to control mothers, young mothers with DS children were more likely to be from rural areas (60%) than urban areas (40%) and of a low socioeconomic status (62%) rather than a high socioeconomic status (38%), and these data match with a previous report from India [25]. These findings may be related to environmental and/or nutritional factors such as folic acid deficiency or pollution by pesticides [26,27].…”
Section: Discussionsupporting
confidence: 89%
“…In Egypt, like other Middle Eastern countries, consanguinity rates fluctuate depending mainly on religious as well as cultural morals, especially in rural areas [22,24]. In the current study, by comparison to control mothers, young mothers with DS children were more likely to be from rural areas (60%) than urban areas (40%) and of a low socioeconomic status (62%) rather than a high socioeconomic status (38%), and these data match with a previous report from India [25]. These findings may be related to environmental and/or nutritional factors such as folic acid deficiency or pollution by pesticides [26,27].…”
Section: Discussionsupporting
confidence: 89%
“…A molecular study found high differences in mean maternal ages between maternal origin cases and paternal origin cases. This demonstrated that the maternal age effect in Down syndrome is limited to maternal nondisjunction and does not provide evidence for a comfortable selection against trisomic fetuses in older women [20,21].…”
Section: Short Tandem Repeat (Str) Markers Used To Infer the Origin Omentioning
confidence: 90%
“…Perhaps this is because most aneuploidies result in spontaneous fetal loss, exposure may precede pregnancy by many years, and generally miscarriages do not receive cytogenetic testing. Several studies have shown an association between maternal socio‐economic status and incidence of Down syndrome births , 84‐86 although this may reflect to some extent differences in the uptake of prenatal diagnosis and termination. Recently, it was noted that the odds of MII error were increased among production workers and within this group, those thought to be exposed to solvents may have been at increased risk for MI error 87 .…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Perhaps this is because most aneuploidies result in spontaneous fetal loss, exposure may precede pregnancy by many years, and generally miscarriages do not receive cytogenetic testing. Several studies have shown an association between maternal socio-economic status and incidence of Down syndrome births, [84][85][86] although this may reflect to some extent differences in the uptake of prenatal diagnosis and termination.…”
Section: Environmental Exposuresmentioning
confidence: 99%